(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
The present research aimed to identify the extent of the practice of science teachers for creative thinking skills in teaching students basic sixth grade in the city of Lattakia, according to the variables: educational qualification. The application note card prepared by the researcher; to identify creative thinking skills included (30) items, and is divided into four axes: fluency, flexibility, originality, and expansion. The research sample has been selected randomly, and applied the note card on (30) teachers for the academic year 2016/ 2017, and descriptive method was used. The results showed that science teachers do not practice creative thinking skills while teaching sixth grade students, and the degree of practice of creative thinking skills was low. Also, the results indicated that there is no statistically significant difference between the average grade of the practice of science teachers for creative thinking skills in the skills of fluency, flexibility, originality, and expansion. And there was no statistically significant difference between the average grade of the practice of science teachers for creative thinking skills according to the variables educational qualification. The research presented several proposals, the most important of which is the work on the development of basic education curricula that are directly related to the skills of creative thinking, as well as conducting studies on the importance of developing creative thinking skills in scientific subjects.